NO-FAULT AUTOMOBILE INSURANCE IN ONTARIO: A LONG AND COMPLICATED STORY - Brown, Craig (Assurances)

(untitled) (HEC Montréal, 1998)
Within the past decade, Ontario has had no fewer than four successive and different regimes of no-fault automobile insurance. Prior to 1990 there was an "add-on" scheme whereby modest first-party no-fault benefits were added on to the tort system without any formal impairment of tort rights. In 1990 the Liberal government introduced a "modified" plan whereby no-fault benefits were increased but tort was modified in that a plaintiff was ineligible to sue unless s/he met a threshold of permanent and serious injury. Subsequently, the eligibility rules for suing in tort (along with benefit levels) have been changed twice with, in each case, separate restrictions for economic and non-economic loss respectively. This paper relates the story of those changes including some of the historical background.